A critically endangered new species of Comanthera from Bahia, Brazil (Paepalanthoideae, Eriocaulaceae) - Echternacht, Livia (Phytotaxa, 2014)
The present work describes and illustrates the new narrowly endemic species Comanthera pignalii (Eriocaulaceae: Paepalanthoideae). This species is restricted to the white-sand environments in the Campos Rupestres at the border of the Serra Geral, in the Espinhaço Mountain Range in Bahia, Brazil. The morphological variation, habitat and geographic distribution of the species are discussed. It is critically endangered according to the IUCN criteria B2ab (i, ii, iii, iv), as evaluated by CNCFlora, the Plant Red List Authority in Brazil. This is the first newly published plant species already officially proposed to the Brazilian Red List.